The relative choice over destiny in a country's long-run economic growth and economic affluence - Esubalew Tadele; Teshome Sirany (Cogent Economics & Finance, 2021)
This paper examines an in-depth and systematic review of why some nations are so rich, while others remain so poor taking into account temporal and spatial dynamics applied for economic growth covariants. Growth literature underscores direct and indirect causes for economic growth. Likewise, economic and non-economic dynamics are thoroughly examined for countries' long-run economic growth and relative wealth accumulation. Endogenous growth theories emphasized that investment in human capital, innovation, and knowledge are major contributors to economic growth. Empirics confirmed that time-variant (such as well-established institutions and their prominent role in devising property rights and policies) gives more emphasis towards shaping a country's long-run economic growth than time-invariant exogenous attributes (like geography). Meanwhile, some nations did not industrialize being geographically advantageous, and the location of the country does not exclusively determine the fate of the nation's economic success. Moreover, state capacity is vital to determining relative wealth accumulation and economic prosperity. The incidence of routine war undermines the fiscal capacity and leads to an extractive form of government and weakens public and private investments, and this sets a country into undesirable outcomes. In a nutshell, time-varying attributes become more flexible to adjust the fate of countries' economic growth and destiny. Furthermore, it requires an intense investigation of what governs a nation's economic successes or failures focusing on country-specific concerns. It needs a close and continuous rectification to reconsider the country's institutional setup and policy frameworks towards endogenously rooted economic growth and development for the relative economic affluence.
Keywords: 330; economic growth; endogenous growth theories; geography; institutions; natural resources; time-variant factors